Strontium carbonate precipitation as a sample preparation technique for isotope ratio analysis of Sr in mineral water and wine by quadrupole‐based inductively coupled plasma mass spectrometry. (20th December 2017) - Dronov, Michail; Koza, Tim; Schwiers, Alexander; Schmidt, Torsten C.; Schram, Jürgen
Abstract : Rationale: The defined origin of food products is nowadays often seen as a marker of quality. Stontium (Sr) isotope ratio determination can be used to verify the origin of such food products and it has thus become an important technique. Wine samples in particular are often investigated using this technique. Sr isotopic ratio measurements are often disturbed by isobaric Rb interference, making a separation procedure necessary. In this investigation a very simple and effective procedure for the separation of Rb + and Sr 2+ ions for Sr isotope ratio determination in mineral water and wine samples was developed. Methods: The classical Sr‐carbonate precipitation reaction for the separation of Sr 2+ ions from highly soluble Rb + ions was used. For liquid samples, such as mineral water or wine, a prior digestion is not required. This sample preparation procedure was successfully applied for Sr isotope measurements on a widely available quadrupole‐based inductively coupled plasma mass spectrometry (ICP‐MS) device in combination with the Concentration‐Gradient‐Method (CGM). Results: The separation achieved Sr/Rb concentration ratios of 50, 000 to 150, 000 in water and wine samples. The addition of Ca 2+ ions to co‐precipitate with the traces of Sr improved the Rb separation and the reproducibility of isotope ratio determination to an uncertainty of ±0 . 4 ‰ (single standard deviation). This sample preparation approach achieved 2 to 6 times better Rb separation than the commonly applied ion‐exchange resin materials. Conclusions: The quality of the separation is only limited by the number of precipitation repetitions. Moreover, the applicability of quadrupole‐based ICP‐MS for the characterisation of samples with respect to their origin by means of Sr isotope ratio determination was demonstrated.